Visual Discourse Analysis of "Cinderella 2021": Exploring Gender Roles, Cultural Elements, and Societal Perspectives - Nurhaliza, Diana Putri; Puspitasari, Dewi; Rosyid, Ocid Abdul (Dinamika Bahasa dan Budaya, 2024)
This research employs visual discourse analysis to dissect the visual elements within the film "Cinderella 2021." The primary objective is to comprehend how the film portrays notions of work, gender roles, and the significance of male and female characters, alongside embedded cultural elements. Through this analysis, the study seeks to unveil the impact of these cinematic depictions on societal perceptions, aiming to contribute to a broader discourse on enhancing perspectives within the community. The recurrent adaptations of Cinderella across various cinematic renditions offer a unique opportunity to scrutinize the evolving perspectives on gender issues throughout time. The narrative serves as a critical lens for dissecting society's attitudes towards female protagonists, their agency, and the nuanced definition of a "happy ending." Consequently, the enduring popularity of Cinderella not only attests to her timeless allure but also positions her as a cultural artifact that prompts contemplation on the intricate dynamics of gender representation within the realm of storytelling. This research sheds light on the film's potential to influence or challenge prevailing societal views, thereby fostering a more informed and progressive dialogue on gender roles and cultural representations. Keywords: Visual Discourse Analysis, Cinderella, social perception, gender roles, cultural representation